IDENTIFIKASI MISKONSEPSI DAN PENYEBABNYA PADA MATERI GELOMBANG STASIONER KELAS XI MENGGUNAKAN FIVE-TIER DIAGNOSTIC TEST - Sylvi Aidiya Febriyana; Winny Liliawati; Ida Kaniawati (Universitas Islam Negeri (UIN) Mataram, 2020)
The purpose of this study is to identify misconceptions and their causes in mechanical waves material using five-tier diagnostic test. The method used in this research is quantitative - descriptive exploratory research. The study was performed in four high schools (SMA) in the city of Bandung with a total of 155 students. The instrument used in this study is five-tier diagnostic test that has 11 items. In determining the misconception, category of students is used acquired from the students answers at the first level up to the fourth level. While the fifth level is used to determine the source of the causes that cause students to experience misconceptions. The results of the research that has been done from 11 items, found 5 misconceptions that meet the criteria including M-6.1, M-7.1, M-8.2, M-8.3, and M-9.2. The cause of misconceptions more caused by self thoughts for every misconceptions findings, because students and average confidence level of the source causes percentage for self thoughts having bigger values than the other source cause. The misconception profiles is 30.97% or 48 students for M-6.1, 12.90% or 20 students for M-7.1, 11.61% or 18 students for M-8.2 , 12.26% or 18 students for M-8.2, and 15.48% or 24 students for M-9.2.